Exploring English Teachers’ Pedagogical Strategy in Implementing Merdeka Curriculum - Hazlinda, Nur; Settiawan, Dodi (Journal of English and Arabic Language Teaching, 2024)
The primary focus of this research was to explore the pedagogical strategies of English teachers in implementing the Kurikulum Merdeka at MTsN 3 Pekanbaru. A qualitative research methodology was employed to examine these strategies. Data was collected through interviews and observations. The subjects of this study were the English teachers at the school, with two teachers selected through purposive sampling. Despite various challenges, the teachers utilized several pedagogical strategies, including discovery learning, technology integration, project-based learning, and differentiated instruction.